1995
DOI: 10.1016/0092-8674(95)90031-4
|View full text |Cite
|
Sign up to set email alerts
|

A drosophila protein that imparts directionality on a chromatin insulator is an enhancer of position-effect variegation

Abstract: The suppressor of Hairy wing (su(Hw)) protein inhibits the function of transcriptional enhancers located distally from the promoter with respect to the location of su(Hw)-binding sites. This polarity is due to the ability of the su(Hw)-binding region to form a chromatin insulator. Mutations in modifier of mdg4 (mod(mdg4)) enhance the effect of su(Hw) by inhibiting the function of enhancers located on both sides of the su(Hw)-binding region. This inhibition results in a variegated expression pattern, and mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
300
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(315 citation statements)
references
References 36 publications
8
300
0
6
Order By: Relevance
“…For transgenic lines, we produced a new vector, YAL, derived from YES (Patton et al, 1992). YAL contains the Antennapedia promoter driving LacZ as reporter, yellow as transformation marker, and flanked by suppressor of Hairywing -binding site boundary sequences (Gerasimova et al, 1995). IRE and upstream regulatory element (URE) fragments were cloned into SalI-XbaI-XhoI targets sites of YAL polylinker, keeping the native orientation relative to the basal promoter.…”
Section: Plasmid Vector Transgenic Lines and Site-directed Mutagenesismentioning
confidence: 99%
“…For transgenic lines, we produced a new vector, YAL, derived from YES (Patton et al, 1992). YAL contains the Antennapedia promoter driving LacZ as reporter, yellow as transformation marker, and flanked by suppressor of Hairywing -binding site boundary sequences (Gerasimova et al, 1995). IRE and upstream regulatory element (URE) fragments were cloned into SalI-XbaI-XhoI targets sites of YAL polylinker, keeping the native orientation relative to the basal promoter.…”
Section: Plasmid Vector Transgenic Lines and Site-directed Mutagenesismentioning
confidence: 99%
“…In flies the most studied insulator element is gypsy, which when placed between two enhancers in a series of enhancers found in the yellow locus, blocks the action of all enhancers distal to the insertion but has no effect on those more proximal to the promoter (3). It has been shown that the insulator action of gypsy is mediated by a DNA-binding protein, Suppressor of Hairy wing [Su(Hw)], and a cofactor, Mod(mdg4) (4). Gypsy elements appear to localize to the nuclear envelope, where they cluster and organize the neighboring chromatin into loop domains (5).…”
mentioning
confidence: 99%
“…The best studied TE insulator comes from the Drosophila gypsy element (7)(8)(9)(10). Gypsy is a long terminal repeat retrotransposon that contains an insulator sequence in its 5′ untranslated region.…”
mentioning
confidence: 99%